PENGARUH PEMBERIAN TERAPI AKTIVITAS KELOMPOK SOSIALISASI (TAKS) TERHADAP INTERAKSI SOSIAL KLIEN GANGGUAN JIWA - Mashuda, Yazid (Politeknik Kesehatan Kemenkes Bengkulu, 2013)
The purpose of this study was to determine the effect of therapy group socialization activities (syntax) of the client's mental disorder of social interaction. This research is a kind of research is pre experimentation with the design of